Colorectal cancer care in the Balkan countries - (:unkn) unknown (My University, 2005)
Purpose: The aim of this survey was to assess the status of colorectal cancer (CRC) care in the Balkans by contacting cancer care specialists in the Balkan Union of Oncology (BUON) member states. Materials and methods: The authors searched the 2004 membership directories of the ASCO and ESMO and identified members from the Balkan countries. They then sent them a 3-page questionnaire via e-mail or fax. Results: Fifty-two responses from 8 countries were received and analysed. The response rate varied from 25% (Turkey) to 3% (Bulgaria). No Bosnian (n=13), Croatian (n=16) and Albanian (n=1) participated. The results showed that, despite variations on the state of development among Balkan countries, there were some striking similarities and also some similar difficulties that CRC specialists are facing in their individual countries. Conclusion: Combined and coordinated efforts at solving some of these common problems may help CRC patients receive better and higher quality care. © 2005 Zerbinis Medical Publications.
Keywords: Balkan countries; Cancer care; Colorectal cancer